The strategy book - Mckeown, Max (Pearson, 2020)
Dr. Max Mckeown is the author of The Strategy Book, winner of the Commuter Read at the Chartered Management Institute Book of the Year 2013 and Amazon's Best Business Books of 2012. He is also author of The Innovation Book, Adaptability: The Art of Winning in an Age of Uncertainty, and four other books. He works as a strategic coach with Fortune 100 companies and is also a popular keynote speaker at conferences worldwide.